NEUROCARDIAC MANIFESTATIONS OF HIV INFECTION: ROLE OF VIRAL PROTEINS, CO-INFECTIONS, AND INFLAMMATORY GENES (Journal of Medical & Health Sciences Review, 2025)
Millions of people worldwide are afflicted by HIV, which can cause major issues with the heart and brain even with effective treatments. HIV proteins (such as gp120 and Tat), infections (such as cytomegalovirus (CMV) and tuberculosis (TB), and genes that cause inflammation (such as TNF-α and IL-6) are examined in this review in relation to conditions like memory loss, confusion (also known as HIV-associated neurocognitive disorders, or HAND), and cardiac problems (such as heart attacks or weak heart muscles). Co-infections exacerbate inflammation, these proteins harm heart and brain cells, and some genes maintain the body's chronic irritability. Doctors are better able to comprehend and diagnose these problems thanks to new technologies like genetic profiling, blood tests, and brain scans. New treatments, such as anti-inflammatory medications and gene therapies, are being tested because HIV medications only partially prevent these issues. In an effort to improve the lives of those living with HIV, we talk about the most recent research, obstacles such as treatment resistance, and strategies to make care more widely available.